Fourth industrial revolution and its impact towards shop houses image / Zalina Samadi ... [et al.] - Samadi, Zalina; Azlan, Nur Izati; Raja Othman, Raja Norashekin; Mohamad, Siti Zabeda (2018)
Conferences and conventions have been organized by the United Nations for Education, Scientific and Culture Organisation (UNESCO) since the early convention in Belgrade. The main aim of the organisation is to create heritage awareness to the participating countries‟ players in their construction industry especially the multi disciplinarian‟s urban builders, urban designers and city authorities. These countries have to create principles to uphold local heritage protection, conservation and revitalisation. Otherwise, new modern buildings are constructed without putting priority on the significance of the existing urban context such as heritage shop houses and heritage buildings. The heritage buildings were randomly demolished due to development pressures from various angles since the past industrial revolution until the new Industrial Revolution 4.0. Therefore, this study zoomed on issues of industrial revolution and globalisation towards outdoor ambiance in between heritage shop houses. The heritage shop houses in this study were limited to shop houses within the core zone of the historic city of the Straits of Malacca; George Town in Pulau Pinang and Melaka. The current condition of the physical and spiritual attributes of the „outdoor space in between the heritage street is in conditional feature that requires urgent revitalisation. The spaces have a high potential to be enhanced as „an urban outdoor living space‟ with magnetic attraction as “a place” for promoting on-street cultural heritage ambiance. The vibrant movement of pedestrian of the observed study area has the regenerative potentials to create an attractive aura with unique, antique and authentic ambience. Thus, the outdoor space quality reflects a generative economic, environmental and social values. With this awareness, the paper discusses the scenario of urban heritage shop houses that require revitalisation. Then, the final section of the discussion presents the constructive attributes to share the setting of our local urban heritage in Malaysia.